Hadith #2582 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
There was a dispute amongst the people of the tribe of Bani `Amr bin `Auf. The Prophet (ﷺ) went to them along with some of his companions in order to make peace between them. The time for the prayer became due but the Prophet (ﷺ) did not turn up; Bilal pronounced the Adhan (i.e. call) for the prayer but the Prophet (ﷺ) did not turn up, so Bilal went to Abu Bakr and said, “The time for the prayer is due and the Prophet (ﷺ) i detained, would you lead the people in the prayer?” Abu Bakr
Grade: Sahih

Hadith #2583 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
It was said to the Prophet (ﷺ) “Would that you see `Abdullah bin Ubai.” So, the Prophet (ﷺ) went to him, riding a donkey, and the Muslims accompanied him, walking on salty barren land. When the Prophet (ﷺ) reached `Abdullah bin Ubai, the latter said, “Keep away from me! By Allah, the bad smell of your donkey has harmed me.” On that an Ansari man said (to `Abdullah), “By Allah! The smell of the donkey of Allah’s Messenger (ﷺ) is better than your smell.” On that a man from `A
Grade: Sahih

Hadith #2584 - Sahih al-Bukhari - Umm Kulthum bint 'Uqba (Sahih al-Bukhari)
That she heard Allah’s Messenger (ﷺ) saying, “He who makes peace between the people by inventing good information or saying good things, is not a liar.”
Grade: Sahih

Hadith #2585 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
Once the people of Quba fought with each other till they threw stones on each other. When Allah’s Apostle was informed about it, he said, “Let us go to bring about a reconciliation between them.”
Grade: Sahih

Hadith #2586 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The following Verse: If a woman fears cruelty or desertion on her husband’s part (i.e. the husband notices something unpleasant about his wife, such as old age or the like, and wants to divorce her, but she asks him to keep her and provide for her as he wishes). (4.128) “There is no blame on them if they reconcile on such basis.”
Grade: Sahih

Hadith #2587 - Sahih al-Bukhari (Sahih al-Bukhari)
A bedouin came and said, “O Allah’s Messenger (ﷺ)! Judge between us according to Allah’s Laws.” His opponent got up and said, “He is right. Judge between us according to Allah’s Laws.” The bedouin said, “My son was a laborer working for this man, and he committed illegal sexual intercourse with his wife. The people told me that my son should be stoned to death; so, in lieu of that, I paid a ransom of one hundred sheep and a slave girl to save my son. Then I asked the learned sc
Grade: Sahih

Hadith #2588 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “If somebody innovates something which is not in harmony with the principles of our religion, that thing is rejected.”
Grade: Sahih

Hadith #2589 - Sahih al-Bukhari - al-Bara' bin Azib bin al-Harith (Sahih al-Bukhari)
When Allah’s Messenger (ﷺ) concluded a peace treaty with the people of Hudaibiya, `Ali bin Abu Talib wrote the document and he mentioned in it, “Muhammad, Allah’s Messenger (ﷺ) .” The pagans said, “Don’t write: ‘Muhammad, Allah’s Messenger (ﷺ)’, for if you were an apostle we would not fight with you.” Allah’s Apostle asked `Ali to rub it out, but `Ali said, “I will not be the person to rub it out.” Allah’s Messenger (ﷺ) rubbed it out and made peace with them o
Grade: Sahih

Hadith #2590 - Sahih al-Bukhari - Al Bara (Sahih al-Bukhari)
When the Prophet (ﷺ) intended to perform `Umra in the month of Dhul-Qada, the people of Mecca did not let him enter Mecca till he settled the matter with them by promising to stay in it for three days only. When the document of treaty was written, the following was mentioned: ‘These are the terms on which Muhammad, Allah’s Messenger (ﷺ) agreed (to make peace).’ They said, “We will not agree to this, for if we believed that you are Allah’s Messenger (ﷺ) we would not prevent you, b
Grade: Sahih

Hadith #2591 - Sahih al-Bukhari - al-Bara' bin Azib bin al-Harith (Sahih al-Bukhari)
On the day of Hudaibiya, the Prophet (ﷺ), the Prophet (ﷺ) made a peace treaty with the Al-Mushrikun on three conditions: 1. The Prophet (ﷺ) would return to them any person from Al-Mushrikun (polytheists, idolaters, pagans). 2. Al-Mushrikun pagans would not return any of the Muslims going to them, and 3. The Prophet (ﷺ) and his companions would come to Makkah the following year and would stay there for three days and would enter with their weapons in cases, e.g., swords, arrows, bows, etc
Grade: Sahih

Hadith #2592 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) set out for the `Umra but the pagans of Quraish prevented him from reaching the Ka`ba. So, he slaughtered his sacrifice and got his head shaved at Al-Hudaibiya, and agreed with them that he would perform `Umra the following year and would not carry weapons except swords and would not stay in Mecca except for the period they allowed. So, the Prophet (ﷺ) performed the `Umra in the following year and entered Mecca according to the treaty, and when he stayed for three day
Grade: Sahih

Hadith #2593 - Sahih al-Bukhari - Sahl bin 'Uthman bin Fars سهل بن عثمان بن فارس (Sahih al-Bukhari)
`Abdullah bin Sahl and Muhaiyisa bin Mas`ud bin Zaid went to Khaibar when it had a peace treaty (with the Muslims).
Grade: Sahih

Hadith #2594 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Ar-Rabi, the daughter of An-Nadr broke the tooth of a girl, and the relatives of Ar-Rabi` requested the girl’s relatives to accept the Irsh (compensation for wounds etc.) and forgive (the offender), but they refused. So, they went to the Prophet (ﷺ) who ordered them to bring about retaliation. Anas bin An-Nadr asked, “O Allah”; Apostle! Will the tooth of Ar-Rabi` be broken? No, by Him Who has sent you with the Truth, her tooth will not be broken.” The Prophet (ﷺ) said, “O Anas! All
Grade: Sahih

Hadith #2595 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
By Allah, Al-Hasan bin `Ali led large battalions like mountains against Muawiya. `Amr bin Al-As said (to Muawiya), “I surely see battalions which will not turn back before killing their opponents.” Muawiya who was really the best of the two men said to him, “O `Amr! If these killed those and those killed these, who would be left with me for the jobs of the public, who would be left with me for their women, who would be left with me for their children?” Then Muawiya sent two Quraishi men
Grade: Sahih

Hadith #2596 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Once Allah’s Messenger (ﷺ) heard the loud voices of some opponents quarreling at the door. One of them was appealing to the other to deduct his debt and asking him to be lenient but the other was saying, “By Allah I will not do so.” Allah’s Messenger (ﷺ) went out to them and said, “Who is the one who was swearing by Allah that he would not do a favor?” That man said, “I am that person, O Allah’s Messenger (ﷺ)! I will give my opponent whatever he wishes.”
Grade: Sahih

Hadith #2597 - Sahih al-Bukhari (Sahih al-Bukhari)
`Abdullah bin Abu Hadrad Al-Aslami owed Ka`b bin Malik some money. One day the latter met the former and demanded his right, and their voices grew very loud. The Prophet (ﷺ) passed by them and said, “O Ka`b,” beckoning with his hand as if intending to say, “Deduct half the debts.” So, Ka`b took half what the other owed him and remitted the other half.
Grade: Sahih

Hadith #2598 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “There is a Sadaqa to be given for every joint of the human body; and for every day on which the sun rises there is a reward of a Sadaqa (i.e. charitable gift) for the one who establishes justice among people.”
Grade: Sahih

Hadith #2599 - Sahih al-Bukhari - Urwa bin 'Abdullah عروة بن عبد الله بن قشير (Sahih al-Bukhari)
Az-Zubair told me that he quarreled with an Ansari man who had participated in (the battle of) Badr in front of Allah’s Messenger (ﷺ) about a water stream which both of them used for irrigation. Allah’s Messenger (ﷺ) said to Az-Zubair, “O Zubair! Irrigate (your garden) first, and then let the water flow to your neighbor.” The Ansari became angry and said, “O Allah’s Messenger (ﷺ)! Is it because he is your cousin?” On that the complexion of Allah’s Messenger (ﷺ) changed (b
Grade: Sahih

Hadith #2600 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
My father died and was in debt. I suggested that his creditors take the fruits (i.e. dates) of my garden in lieu of the debt of my father, but they refused the offer, as they thought that it would not cover the full debt. So, I went to the Prophet (ﷺ) and told him about it. He said (to me), “When you pluck the dates and collect them in the Mirbad (i.e. a place where dates are dried), call me (Allah’s Messenger (ﷺ)).” Finally he came accompanied by Abu Bakr and `Umar and sat on the date
Grade: Sahih

Hadith #2601 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
That Ka`b bin Malik told him that in the lifetime of Allah’s Messenger (ﷺ) he demanded his debt from Ibn Abu Hadrad in the Mosque. Their voices grew louder till Allah’s Messenger (ﷺ) heard them while he was in his house. So he lifted the curtain of his room and called Ka`b bin Malik saying, “O Ka`b!” He replied, “Labbaik! O Allah’s Messenger (ﷺ)!” He beckoned to him with his hand suggesting that he deduct half the debt. Ka`b said, “I agree, O Allah’s Messenger (ﷺ)!” A
Grade: Sahih